2018
DOI: 10.1038/s41598-018-32849-6
|View full text |Cite
|
Sign up to set email alerts
|

The terpenes of leaves, pollen, and nectar of thyme (Thymus vulgaris) inhibit growth of bee disease-associated microbes

Abstract: Honey bees are highly prone to infectious diseases, causing colony losses in the worst case. However, they combat diseases through a combination of their innate immune system and social defence behaviours like foraging for health-enhancing plant products (e.g. nectar, pollen and resin). Plant secondary metabolites are not only highly active against bacteria and fungi, they might even enhance selective foraging and feeding decisions in the colony. Here, we tested six major plant terpenes and their corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 87 publications
0
25
0
3
Order By: Relevance
“…The bee forage able thyme product terpenes (mainly from pollen) were an antibiotic that reduces the growth of bee disease-associated with bacteria effectively. This is a further step forward in understanding the complex pathogenpollinator-plant network (Wiese et al, 2018).…”
Section: Pesticidesmentioning
confidence: 96%
“…The bee forage able thyme product terpenes (mainly from pollen) were an antibiotic that reduces the growth of bee disease-associated with bacteria effectively. This is a further step forward in understanding the complex pathogenpollinator-plant network (Wiese et al, 2018).…”
Section: Pesticidesmentioning
confidence: 96%
“…Their antimicrobial activity also depends on their chemical composition (Omonijo et al, 2018). The most effective components of essential oils are predominantly terpenes, terpenoids and phenolic substances (Wiese et al, 2018;Olmedo et al, 2018;Pichersky a Raguso, 2018). Based on the above we evaluated the chemical composition of tested EOs by the GC-MS analysis.…”
Section: Chemical Analysis Of Essential Oilsmentioning
confidence: 99%
“…Tea tree oil nanoparticles (Santos et al, 2014), Malva sylvestris oil (Cecotti et al, 2016), aqueous and ethanolic extracts of Cinnamomum spp. and Persian salvadora (Hashish et al, 2016), macelignan and corosolic acid (Kim et al, 2018), terpenes of Thymus vulgaris (Wiese et al, 2018), among others, have been shown to have significant antibacterial effects against M. plutonius. The use of extracts and essential oils for integrated EFB treatment is promising and stimulates the search for other bioactive plant phytochemicals with bactericidal capacity and low toxicity for bees.…”
Section: Efb Controlmentioning
confidence: 99%